Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
The answer is C.
Explanation:
(First, make sure the to finish solving the quadratic equation)
x^2 + 2x - 16 = 12x
x^2 - 10x - 16 = 0
(a, b and c are the coefficients of x^2, x and the constant respectively)
a = 1, b = -10, c = -16
(We can substitute this into the quadratic equation. +- means + or -)
x = [- b +- sqrt(b^2 - 4ac)]/2a
= [- (-10) +- sqrt(100 + 64)]/2
= [10 +- sqrt(164)]/2
(So C is the answer)
Explanation:
(First, make sure the to finish solving the quadratic equation)
x^2 + 2x - 16 = 12x
x^2 - 10x - 16 = 0
(a, b and c are the coefficients of x^2, x and the constant respectively)
a = 1, b = -10, c = -16
(We can substitute this into the quadratic equation. +- means + or -)
x = [- b +- sqrt(b^2 - 4ac)]/2a
= [- (-10) +- sqrt(100 + 64)]/2
= [10 +- sqrt(164)]/2
(So C is the answer)
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.